Analisis Efektivitas Metode Diskusi dalam Meningkatkan Pemahaman Siswa pada Mata Pelajaran Ekonomi - Andi Nur Asrah Bahar; Hamka Hamka; Sahiruddin Sahiruddin (Journal on Education, 2025)
This study aims to determine the effectiveness of the discussion method in reminding students of their understanding of economics subjects. The type of research used is a quantitative research method. The data obtained and processed were the results of questionnaire answers from students in grade XI IPS SMAN 3 Bone. The data collection techniques used in this study are observation, documentation and questionnaires by going directly to the research location. The results of the research obtained by the author are that the variable of the discussion method (X) is effective in improving students' understanding (Y) in the economics subject of class XI students of Social Sciences SMAN 3 Bone. This means that the hypothesis (Ha) is accepted, because the tcal value > ttable or 7.779 > 1.685 is a sig value of 0.000 < 0.05. Thus the hypothesis in this study (Ha) is accepted. The discussion method plays an important role in improving students' understanding of economics in class XI IPS SMAN 3 Bone. This means that the hypothesis (Ha) is accepted, because the tcal value > ttable or 7.779 > 1.685 is a sig value of 0.000 < 0.05. Thus the hypothesis in this study (Ha) is accepted. The discussion method plays an important role in improving students' understanding of economics in class XI IPS SMAN 3 Bone. Through discussions, students can share their experiences and knowledge about economic concepts, while honing critical thinking skills. Discussions create an inclusive learning environment that encourages students' understanding and active engagement.